DEVELOPMENT OF COLLECTIVE TRADEMARK FOR BATIK INDUSTRY IN KAMPUNG BATIK LAWEYAN (LAWEYAN BATIK’S VILLAGE), SOLO - Sardjono, Agus; Prasetyo, Brian Amy; Larasati, Derezka Gunti (Indonesia Law Review, 2015)
Previous research found that the individual trademark system has not been effectively utilized to support the business of batik Smal Medium Enterprises (SMEs), particularly in several batik industry centers in Java, namely Bantul in Yogyakarta province, Kauman in Pekalongan and Laweyan in Solo. However, the fact that those SMEs gather in a community, organization, or kinships bring potentials for development of collective trademarks, which can address the problems that individual trademark cannot anticipate. The development of collective trademark can also be a strategy to anticipate the free-trade ‘attack,’ i.e. imported textiles with batik patterns/motifs; which are not the original Indonesian batik. In regards to that, Indonesian batik SMEs need to be nurtured and encouraged to register their own collective trademarks and to build their branding infrastructure, through local batik community’s standardization, and collective batik labeling. This present research focuses on the development of collective trademark utilization by one longknown batik community in Kampung Batik Laweyan, Solo, as a strategy to enable them to compete with imported batik-printed textiles, as well as to protect their traditional batik cultural heritage.